Ilich's Educational Philosophy in the Perspective of Islamic Educational Philosophy: A Critical Study and its Relevance in Contemporary Era - Istanto, Dwi; Arroisi, Jarman (Proceeding International Conference on Religion, Science and Education, 2025)
The research conducted by this researcher aims to conduct a critical review of Ivan Ilich's educational philosophy based on Islamic educational philosophy and its relevance in the contemporary era. This study is a study based on literature review or can be called a qualitative study. In this study, the data used is qualitative data. The findings are that there are several Ivan Ilich rules that do not conflict with Islamic educational philosophy, such as understanding learning as an activity of spreading knowledge and equal rights to learn without discrimination. However, there are also principles that are considered inconsistent, such as the goal of Islamic education which prioritizes noble morals, while Ivan Ilich's educational goals emphasize social justice. In conclusion, in the context of contemporary education, Ivan Ilich's educational philosophy can support active, creative, dynamic, and confident attitudes, but it needs to be balanced with education based on spirituality and faith.